The Effect of Solvent-Modification on the Physicochemical Properties of ZnO Nanoparticles Synthesized by Sol-Gel Method - Zainab Yousif Shnain; Manal Afham Toma; Basheer A. Abdulhussein; Najat J. Saleh; Mohammed Ibrahim; Nerran Manuel; Abbner Mahmood (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
This study investigated the solvent effect on the synthesis of Zinc Oxide (ZnO) nanoparticle using sol-gel method. Zinc acetate dihydrate and oxalic acid were used as a chemical precursor for the synthesis of the ZnO nanoparticle considering the effects of various solvents. The effect of using water, propanol, or ethanol as solvent during the synthesis were examined. The resultant gel in the aqueous and organic moderate solvent was thermally cracked into ZnO nanoparticles at 450 °C under atmospheric pressure. The results showed that the solvent type has a significant effect on the morphology and particles size of the ZnO nanoparticles synthesized. Atomic Force Microscopy (AFM) was used to investigate the microstructure of the nanoparticles. The crystalline and chemical structure of the prepared ZnO nanoparticle were studied by X-ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR). The average diameter of nano-size particles obtained for ethanol, propanol and water are 79.55 nm, 83.86 nm and 85.59 nm, respectively. ZnO particles showed higher degree of crystalline in water compared to other solvents under current investigation. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).